2022
DOI: 10.1002/mco2.173
|View full text |Cite
|
Sign up to set email alerts
|

Targeting epigenetic regulators for inflammation: Mechanisms and intervention therapy

Abstract: Emerging evidence indicates that resolution of inflammation is a critical and dynamic endogenous process for host tissues defending against external invasive pathogens or internal tissue injury. It has long been known that autoimmune diseases and chronic inflammatory disorders are characterized by dysregulated immune responses, leading to excessive and uncontrol tissue inflammation. The dysregulation of epigenetic alterations including DNA methylation, posttranslational modifications to histone proteins, and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 377 publications
(828 reference statements)
1
10
0
Order By: Relevance
“…Gene expression is tightly regulated by dynamic chromatin states controlled by multiple families of chromatin regulators including the modifiers of DNA methylation, histone methylation and ubiquitylation, and chromatin remodeling complexes. The mutation of chromatin regulators is frequently observed in human cancer and thus these regulators are attractive drug targets (43)(44)(45)(46)(47)(48). Our results also highlight the importance of chromatin regulators in cancer by showing D121Y mutation of CHRAC1 in CRCs, which has a great challenge in POLE3 interaction and the recruitment of KU70/80 complex in DDR.…”
Section: Discussionsupporting
confidence: 63%
“…Gene expression is tightly regulated by dynamic chromatin states controlled by multiple families of chromatin regulators including the modifiers of DNA methylation, histone methylation and ubiquitylation, and chromatin remodeling complexes. The mutation of chromatin regulators is frequently observed in human cancer and thus these regulators are attractive drug targets (43)(44)(45)(46)(47)(48). Our results also highlight the importance of chromatin regulators in cancer by showing D121Y mutation of CHRAC1 in CRCs, which has a great challenge in POLE3 interaction and the recruitment of KU70/80 complex in DDR.…”
Section: Discussionsupporting
confidence: 63%
“…Our previous research elucidated that KAT2A was overexpressed in RA synovium, and pharmacological inhibition of KAT2A significantly alleviated inflammation in collagen-induced arthritis (CIA) mice. 96 What is more, the dynamic balance of histone lysine methyltransferases (KMT)/histone lysine demethylase (KDM) regulates the methylation of H3K4, H3K36, and H3K79 to promote gene transcription and the methylation of H3K9, H3K27 and H4K20 to suppress gene transcription. 122 Studies identified an upregulation of twelve KMTs and four KDMs in RA-FLS, leading to significant changes in histone methylation patterns.…”
Section: Histone Modificationmentioning
confidence: 99%
“…In addition to cancers, 184,185 epigenetic targets also play significant roles in other human diseases, 186 such as inflammation, 187 viral infections, 188 and central nervous system (CNS) disorders. 189 For example, bromodomain-containing protein 4 (BRD4), a key epigenetic regulator, has been implicated in cancers, 190 viral infections, 191−194 and inflammations, 195−197 and their function inhibition by small molecules resulted in anticancer, antiviral, and anti-inflammatory effects, 198,199 which has also been clarified in our previous work.…”
Section: ■ the Roles Of Nsd2 In Other Human Diseasesmentioning
confidence: 99%